2022
DOI: 10.3390/vaccines10030425
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Take the Booster Vaccine in a Nationally Representative Sample of Danes

Abstract: We estimate the willingness to take the booster dose in a representative sample of Danes. We estimate an overall willingness in the adult Danish population of about 87 percent and a willingness of about 95.5 percent among primary vaccine takers. Moreover, we show that these percentages are significantly lower among younger populations, as well as among groups who do not see COVID-19 as a threat to society, those who do not feel that they have the ability to follow recommendations (‘self-efficacy’), those who d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 26 publications
4
33
1
Order By: Relevance
“…The literature suggests that older age, influenza vaccination, and confidence in COVID-19 vaccines are associated with the willingness of the general public to accept a booster, while adverse side effects after previous COVID-19 vaccination and concerns for serious side effects after booster doses are associated with vaccine hesitancy [12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The literature suggests that older age, influenza vaccination, and confidence in COVID-19 vaccines are associated with the willingness of the general public to accept a booster, while adverse side effects after previous COVID-19 vaccination and concerns for serious side effects after booster doses are associated with vaccine hesitancy [12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Though previous research has examined booster willingness in the United States and abroad at a national level, understanding the attitudes and beliefs of sub-populations is key to addressing vaccine and booster rates. ( Jørgensen et al, 2022 , Rzymski et al, 2021 , Tung et al, 2022 , Yadete et al, 2021 ) Some researchers have begun to explore the attitudes and beliefs in key populations. Giuseppe et al examined attitudes of incarcerated people in Italy, where they identified younger incarcerated people, those who do not perceive the severity of the disease, and are not aware of the availability of the vaccine as key target groups for public health vaccination campaigns.…”
Section: Discussionmentioning
confidence: 99%
“…While numerous articles have reported on booster willingness internationally, booster rates remain low in the United States. ( Jørgensen et al, 2022 , Rzymski et al, 2021 , Tung et al, 2022 , Yadete et al, 2021 ) Despite the Centers for Disease Control and Prevention (CDC) recommending the booster for all Americans ages 12 years and older who has completed the primary COVID-19 vaccine series, as of May 2022 only 30.5% of the United States population has received at least one booster. ( COVID-19 vaccine boosters administered per 100 people., 2022 ) The low uptake of COVID-19 boosters suggests the need for a more in-depth understanding of attitudes and concerns about getting booster doses in diverse populations.…”
Section: Introductionmentioning
confidence: 99%
“…These ndings are similar to studies assessing willingness for booster vaccines in Europe and North America. [21][22][23][24][25][26] This is a reassuring nding for public health authorities, as the success of a vaccination program relies in part on the willingness of a population to accept available vaccines. The high primary dose uptake and willingness to receive a booster dose among our study population may be attributed to community engagement programs, which improved accessibility for different communities by providing information in several languages in written and oral formats and outreach vaccination clinics for speci c communities.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that information need, subjective norms, perceived risk, and information channels can affect COVID-19 vaccine willingness, but they did not ask participants explicitly about exposure to the concerning news. 12,21,22,24,25,29,30,[33][34][35][36] The effect of exposure to concerning news on willingness to receive a booster dose is an area that needs further research especially with the introduction of new vaccines. Our nding may be related to explicitly asking respondents about the news they had consumed in recent months.…”
Section: Discussionmentioning
confidence: 99%